(untitled) (American Journal of Islam and Society, 2016)
Books Reviewed: Mehmet Zeki Kuşoğlu, The Ottoman Touch: Traditional Decorative Arts and Crafts (Istanbul: Blue Dome Press, 2015); Mehmet Zeki Kuşoğlu, Silver in Turkish Art (Istanbul: Blue Dome Press, 2015); Sema Onat, Islamic Art of Illumination: Classical Tazhib from Ottoman to Contemporary Times (Istanbul: Blue Dome Press, 2015); Laurelie Rae, Islamic Art and Architecture: Memories of Seljuk and Ottoman Masterpieces (Istanbul: Blue Dome Press, 2015). The unusual aspect connecting these four books is not the fact that they share the same publisher or even the same general scope of Turkish arts, but that they have been authored by practicing artists who have featured some of their original works between their covers. Blue Dome Press, a relatively new publisher, has offices in the major western cities; however, all of the printing done in Istanbul. In addition, the majority of its publications, which range from Turkish cooking to fiction, from current affairs to various arts, focus on some aspect of Turkish culture. By supporting the publication of these texts, one gets the sense that various sectors of Turkish society continue to value the traditional and important historical contributions that the featured and other contemporary artists continue to make to the national culture. The three artists featured in this review (one is the author of two books) come from different backgrounds that have enabled them to practice their art today. Mehmet Zeki Kuşoğlu author of The Ottoman Touch: Traditional Decorative Arts and Crafts and Silver in Turkish Art, has practiced the crafts of silverwork and other art forms based on traditional methods for over forty years. During his career, he has apprenticed with craftsmen – he identifies them by name – and completed two art degrees in Turkey. His efforts to understand, reconcile, and ultimately interpret the country’s historical craft methods through his own creations lends a tremendous insight into the meanings and processes of crafts, one that brings them palpably alive. Sema Onat, author ...